TiC / Fe / Ni / Al metal ceramic and preparation method thereof

Through the preparation method of TiC/Fe/Ni/Al metal cermet, the problems of low hardness and insufficient bending strength of existing metal cermet materials at high temperatures are solved, and the improvement of high hardness, denseness and good thermal conductivity are achieved, and the Preparation cost, suitable for electrical equipment.

CN119220843APending Publication Date: 2024-12-31PANZHIHUA UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411341097.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-25
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

The existing cermet materials have low hardness at high temperatures, insufficient flexural strength, and high production cost, which limits their application in electrical equipment.

Method used

TiC/Fe/Ni/Al metal cermet is prepared by ball milling, drying, pressing and staged heating of Fe powder, Al powder and Ni powder, TiC/Fe/ is prepared with high hardness and good density. Ni/Al cermet.

Benefits of technology

The high hardness, bending strength and thermal conductivity of TiC/Fe/Ni/Al cermet has been improved, while reducing the preparation cost, avoiding deformation and unqualification caused by rapid heating, and the product structure is uniform.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119220843A_ABST
    Figure CN119220843A_ABST
Patent Text Reader

Abstract

The invention relates to TiC / Fe / Ni / Al metal ceramic and a preparation method thereof, and belongs to the technical field of inorganic metal materials. The preparation method of the TiC / Fe / Ni / Al metal ceramic comprises the steps that A, Fe powder, Al powder and Ni powder are mixed and then subjected to ball milling, and a mixture 1 is obtained; b, adding TiC powder into the mixture 1, and continuing ball milling to obtain a mixture 2; c, adding polyethylene glycol into the mixture 2, and uniformly mixing to obtain a mixture 3; d, drying the mixture 3 at 70 DEG C for 7-8 hours; and E. carrying out compression molding on the mixture 3 dried in the step D. The TiC / Fe / Ni / Al metal ceramic is high in hardness and good in comprehensive performance such as compactness, bending strength and heat-conducting property.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a TiC / Fe / Ni / Al metal ceramic and a preparation method thereof, belonging to the technical field of inorganic metal materials. Background Art

[0002] Cermet is a two-phase mechanical composite material that can maintain the original physical properties of the metal phase and has excellent properties such as good wear resistance, corrosion resistance, high strength and high temperature stability. It is widely used in aerospace, automobile manufacturing, chemical industry and other fields to manufacture high-temperature parts, wear-resistant parts, anti-corrosion coatings, etc. Cermet materials have two phases. The first is the refractory phase, which can maintain high hardness, high melting point, high temperature resistance, impact resistance and non-melting characteristics in the arc. This phase acts as a skeleton in cermets and can be formed by metals (such as molybdenum, tungsten and metal oxides). The second phase is the current-carrying phase, which can conduct electricity and heat. Compared with the refractory phase, it has a lower melting point and will melt into liquid at the high temperature generated by the arc. It can fill the gaps formed by the skeleton to prevent the molten metal from splashing, thereby extending the service life of the composite material and reducing wear. Traditional contact materials play an important role in electrical equipment, and their selection depends on the specific application requirements and environmental conditions. With the continuous development of technology, the research and application of new contact materials are also emerging, providing new possibilities for improving the performance of electrical equipment and energy saving and emission reduction. Among the properties required for contact materials, cermets can meet a large part of them. Titanium carbide-based cermets are composite materials composed of metal and titanium carbide. They are very important composite materials and structural materials. Titanium carbide-based cermets have great potential as contact materials and can be used in electrical equipment that requires high performance and long life.

[0003] CN103981418A discloses a TiC / TiB2 / Al / Cu electrical contact material and a preparation method thereof. The material is prepared from the following raw materials in weight ratio: 28-40 parts of titanium carbide, 10-20 parts of titanium boride, 10-22 parts of aluminum, 20-54 parts of copper, and 1-3 parts of adhesive. The material reduces the amount of Cu, increases the content of strengthening phase titanium carbide and titanium boride, improves the wettability of titanium carbide and copper, has high density, low contact resistance, good resistance to fusion welding, and high hardness.

[0004] CN111028978A discloses a (Ti, Mo) C / TiB2 / Al / Cu electrical contact material and a preparation method thereof. The material is prepared from the following raw materials in weight ratio: 40-70 parts of titanium molybdenum carbide, 15-18 parts of titanium boride, 5-10 parts of aluminum, 10-15 parts of copper, and 1-2 parts of adhesive. The bending strength is significantly improved while maintaining high density. In addition, the preparation process of the material of the present invention is simple and the cost is low.

[0005] CN116949335A discloses a low-cost titanium carbide-based cermet, which is prepared from raw material powders in the following weight ratio: TiC is fixed at 27 parts, Cu is fixed at 10 parts, Al and Ni are 63 parts in total, wherein Al is 43-58 parts, Ni is 5-20 parts, and also includes adhesive polyethylene glycol, wherein the polyethylene glycol is 1%-3% of the total weight of the above powders. The present invention uses Al, Cu and Ni as the main additive elements, which are all commonly used metals, and the material cost is low. Among them, selecting more Al powder can reduce the sintering temperature of the powder, and realize sintering at a lower temperature to obtain a TiC-based cermet with excellent performance, and the production cost is low; the present invention uses Al to improve the wettability between Cu and TiC, reduce the porosity, and improve the compactness of the material. At the same time, the intermediate alloys generated by Al and Cu and Al and Ni are used to improve the strength of the cermet, and it has the advantages of high density, excellent bending strength, excellent thermal conductivity, etc. However, its hardness is low, and its scope of use is subject to certain restrictions. Summary of the invention

[0006] The first object of the present invention is to provide a novel method for preparing TiC / Fe / Ni / Al metal ceramics.

[0007] To achieve the first object of the present invention, the preparation method of the TiC / Fe / Ni / Al metal ceramic comprises:

[0008] A. Fe powder, Al powder and Ni powder were mixed and ball-milled to obtain a mixture 1;

[0009] B. Add TiC powder to mixture 1 and continue ball milling to obtain mixture 2;

[0010] C. adding polyethylene glycol to mixture 2 and mixing well to obtain mixture 3;

[0011] D. drying the mixture 3 at 70° C. for 7 to 8 hours;

[0012] The mixture 3 after drying in step ED is pressed into shape;

[0013] F. Under argon protection, the pressed mixture is heated to 950°C to 1050°C in stages 3, kept warm for at least 180 minutes, and cooled to below 200°C with the furnace to obtain a TiC / Fe / Ni / Al metal ceramic, wherein the staged heating is firstly heated from room temperature to 350°C at a heating rate of 10°C / min and kept warm for 30 minutes, then heated to 650°C at a heating rate of 7.5°C / min and kept warm for 60 minutes, and finally heated to a sintering temperature of 950°C to 1050°C at a heating rate of 5°C / min to 6°C / min;

[0014] By weight, TiC powder is fixed at 32.5 parts, Al powder is fixed at 42.5 parts, Fe powder and Ni powder are 25 parts in total, of which Fe powder is 1.25-11.25 parts, Ni powder is 23.75-13.75 parts, and polyethylene glycol is 1%-3% of the total weight of the above powders.

[0015] In a specific embodiment, the Fe powder is reduced iron powder with a purity greater than 98.0% and a particle size of 200-600 meshes.

[0016] In a specific embodiment, the Ni powder is electrolytic nickel powder with a purity greater than 99.0% and a particle size of 200-800 mesh.

[0017] In a specific embodiment, the purity of the Al powder is greater than 99.0%, and the particle size is 400-600 mesh.

[0018] In a specific embodiment, the purity of the TiC powder is greater than 99.0%, and the average particle size is 1.0 μm.

[0019] In a specific implementation manner, the rotation speed of the ball mill is controlled at 300 r / min to 350 r / min, and the ball milling of step A and step B is respectively performed for more than 60 minutes.

[0020] In a specific embodiment, the pressure of the compression molding in step E is 16-20 MPa.

[0021] In a specific embodiment, the flow rate of the argon gas in step F is controlled at 60-100 ml / min.

[0022] A second object of the present invention is to provide a TiC / Fe / Ni / Al metal ceramic.

[0023] To achieve the second purpose of the present invention, the TiC / Fe / Ni / Al metal ceramic is prepared by the preparation method of the TiC / Fe / Ni / Al metal ceramic as described above. Preferably, the hardness of the TiC / Fe / Ni / Al metal ceramic is above 38HRC, and more preferably above 45HRC.

[0024] In a specific embodiment, the TiC / Fe / Ni / Al metal ceramic has a relative density of more than 99%, a flexural strength of more than 21 MPa, and a thermal conductivity of more than 0.5 W / (m·K), preferably a flexural strength of more than 45 MPa and a thermal conductivity of more than 4.5 W / (m·K).

[0025] Beneficial effects:

[0026] 1. The wettability of Fe, Ni and TiC is not good. In the present invention, TiC powder is fixed at 32.5 parts by weight, Al powder is fixed at 42.5 parts by weight, Fe powder and Ni powder are 25 parts in total, of which Fe powder is 1.25-11.25 parts, Ni powder is 23.75-13.75 parts, and polyethylene glycol is 1-3 parts of the total weight of the above powders. In combination with the preparation method of the present invention, the wettability of Fe and Ni with TiC is improved, and the prepared TiC / Fe / Ni / Al metal ceramic has high hardness and good comprehensive properties such as density, flexural strength and thermal conductivity.

[0027] 2. The process of the present invention as a whole can ensure the coordination of the thermal expansion differences of different powders during the heating process, prevent deformation and cracking of metal ceramics due to rapid heating, and the product has no unqualified phenomena such as segregation and stratification, and the structure is uniform after sintering.

[0028] 3. The method of the present invention has low production cost. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 The XRD diffraction pattern of the TiC / Fe / Ni / Al metal ceramic of Example 1 of the present invention;

[0030] Figure 2 This is a scanning electron microscope image of Example 1 of the present invention at a magnification of 2000×.

[0031] (a) has an iron content of 0.5 g and a nickel content of 9.5 g, (b) has an iron content of 1.5 g and a nickel content of 8.5 g, (c) has an iron content of 2.5 g and a nickel content of 7.5 g, and (d) has an iron content of 3.5 g and a nickel content of 6.5 g. DETAILED DESCRIPTION

[0032] To achieve the first object of the present invention, the preparation method of the TiC / Fe / Ni / Al metal ceramic comprises:

[0033] A. Fe powder, Al powder and Ni powder were mixed and ball-milled to obtain a mixture 1;

[0034] B. Add TiC powder to mixture 1 and continue ball milling to obtain mixture 2;

[0035] C. adding polyethylene glycol to mixture 2 and mixing well to obtain mixture 3;

[0036] D. drying the mixture 3 at 70° C. for 7 to 8 hours;

[0037] The mixture 3 after drying in step ED is pressed into shape;

[0038] F. Under argon protection, the pressed mixture is heated to 950°C to 1050°C in stages 3, kept warm for at least 180 minutes, and cooled to below 200°C with the furnace to obtain a TiC / Fe / Ni / Al metal ceramic, wherein the staged heating is firstly heated from room temperature to 350°C at a heating rate of 10°C / min and kept warm for 30 minutes, then heated to 650°C at a heating rate of 7.5°C / min and kept warm for 60 minutes, and finally heated to a sintering temperature of 950°C to 1050°C at a heating rate of 5°C / min to 6°C / min;

[0039] By weight, TiC powder is fixed at 32.5 parts, Al powder is fixed at 42.5 parts, Fe powder and Ni powder are 25 parts in total, of which Fe powder is 1.25-11.25 parts, Ni powder is 23.75-13.75 parts, and polyethylene glycol is 1%-3% of the total weight of the above powders.

[0040] In a specific embodiment, the Fe powder is reduced iron powder with a purity greater than 98.0% and a particle size of 200-600 meshes.

[0041] In a specific embodiment, the Ni powder is electrolytic nickel powder with a purity greater than 99.0% and a particle size of 200-800 mesh.

[0042] In a specific embodiment, the purity of the Al powder is greater than 99.0%, and the particle size is 400-600 mesh.

[0043] In a specific embodiment, the purity of the TiC powder is greater than 99.0%, and the average particle size is 1.0 μm.

[0044] By controlling the particle size of the raw material powder, the uniformity of the mixed material can be improved, and a dense compact can be obtained during the pressing process. In the subsequent sintering process, the metal powder can be more easily sintered and fused together, thereby improving the structural strength.

[0045] In a specific implementation manner, the rotation speed of the ball mill is controlled at 300 r / min to 350 r / min, and the ball milling of step A and step B is respectively performed for more than 60 minutes.

[0046] In a specific embodiment, the pressure of the compression molding in step E is 16-20 MPa.

[0047] In a specific embodiment, the flow rate of the argon gas in step F is controlled at 60-100 ml / min.

[0048] To achieve the second purpose of the present invention, the TiC / Fe / Ni / Al metal ceramic is prepared by the preparation method of the TiC / Fe / Ni / Al metal ceramic as described above. Preferably, the hardness of the TiC / Fe / Ni / Al metal ceramic is above 38HRC, and more preferably above 45HRC.

[0049] In a specific embodiment, the TiC / Fe / Ni / Al metal ceramic has a relative density of more than 99%, a flexural strength of more than 21 MPa, and a thermal conductivity of more than 0.5 W / (m·K), preferably a flexural strength of more than 45 MPa and a thermal conductivity of more than 4.5 W / (m·K).

[0050] The specific implementation modes of the present invention are further described below in conjunction with embodiments, but the present invention is not limited to the scope of the embodiments.

[0051] Example 1

[0052] like Figure 1 As shown, the XRD diffraction patterns when the sintering temperature is 1050°C are, from bottom to top, samples 2-1, 2-2, 2-3, 2-4, 2-5, 2-6, 2-7, 2-8, and 2-9, respectively. The sample composition increases from 0.5g iron powder and 9.5g nickel powder in sample 2-1, with the iron powder content increasing by 0.5g and the nickel powder content decreasing by 0.5g, to 4.5g iron powder and 5.5g nickel powder in sample 2-9.

[0053] The purity of the reduced iron powder is greater than 98.0%, and the particle size is 200-600 meshes. The purity of the electrolytic nickel powder is greater than 99.0%, and the particle size is 200-800 meshes. The purity of the Al powder is greater than 99.0%, and the particle size is 400-600 meshes. The purity of the TiC powder is greater than 99.0%, and the average particle size is 1.0 μm. The iron powder, the nickel powder, and the aluminum powder are first ball-milled in a ball mill for 60 minutes, and then the TiC powder is added to the mixed metal powder and ball-milled for another 60 minutes. The speed of the ball mill is controlled at 300 r / min-350 r / min. Finally, the uniformly mixed powder is put into a mortar, polyethylene glycol is added, and the mixing is continued. The polyethylene glycol is 1%-3% of the total weight of the above powders. The mixed powder mixed with polyethylene glycol is placed in an oven and dried at 70°C for 7 to 8 hours, the powder is loaded into a specific mold, and pressed in a tablet press with a pressing pressure of 16 to 20 MPa, and demolded to obtain a molded product. Under argon protection, the pressed product is heated in three stages, first at a heating rate of 10°C / min, from room temperature to 350°C and kept warm for 30 minutes, then at a heating rate of 7.5°C / min to 650°C and kept warm for 60 minutes, and finally at a heating rate of 6°C / min to 1050°C, kept warm for 180 minutes, and cooled to below 200°C with the furnace to prepare TiC / Fe / Ni / Al metal ceramics.

[0054] Figure 1 It can be seen that the composition of each group of samples changes and the number of peaks changes, and the generation and change of the sample compounds at the sintering temperature of 1050℃ can be obtained. From the XRD spectrum, it can be seen that the main generated phase in samples 2-1, 2-2, 2-3, and 2-4 is Al3Ni, and as the iron content increases, Al3Ni gradually decreases and disappears when the iron content is 2.5g and the nickel content is 7.5g. After that, as the iron content increases, Al3Ni appears in samples 2-6, 2-7, 2-8, and 2-9. 13 Fe4 phase.

[0055] Figure 2 (a), (b), (c), and (d) are scanning electron microscope images at a sintering temperature of 1050°C, when the iron content increases from 0.5g by 1g to 3.5g, and the nickel content decreases from 9.5g by 1g to 6.5g, respectively, at a magnification of 2000×. The structure is relatively dense, with uniform and fine pores as the main distribution. The core is mainly TiC matrix phase, and a continuous bonding phase is distributed around TiC. The composition of these bonding phases is Al3Ni or Al 13 Fe4.

[0056] Example 2

[0057] 1.25 parts of Fe powder, 23.75 parts of Ni powder, 42.5 parts of Al powder, mixed ball mill speed of 310r / min, time for 60min, then mixed with 32.5 parts of TiC powder, speed of 300r / min, time for 60min, move the mixed powder into a mortar, add 1.25 parts of polyethylene glycol and stir to mix, then keep it in an oven at 70℃ for 7h, then press it under a pressure of 20MPa, take out the pressed block and put it into a tubular furnace for argon protection sintering, the argon flow rate is controlled to 60ml / min. First, the heating rate is controlled to 10℃ / min, from room temperature to 350℃ and keep it for 30 minutes, then the heating rate is controlled to 7.5℃ / min, rise to 650℃ and keep it for 60 minutes, finally, the heating rate is controlled to 6℃ / min to rise to the sintering temperature of 1050℃, keep it for 180 minutes, wait for the temperature to drop to 200℃ and then take out the sample. The measured performance indicators are shown in Table 1.

[0058] Example 3

[0059] 2.5 parts of Fe powder, 22.5 parts of Ni powder and 42.5 parts of Al were mixed and milled at a speed of 320r / min for 60min, and then mixed with 32.5 parts of TiC powder at a speed of 305r / min for 60min. The mixed powder was moved into a mortar, 1.5 parts of polyethylene glycol were added and stirred, and then pressed under a pressure of 20MPa. The pressed block was taken out and put into a tube furnace for argon protection sintering, and the argon flow rate was controlled to 70ml / min. First, the heating rate was controlled to be 10℃ / min, from room temperature to 350℃ and kept warm for 30 minutes, then the heating rate was controlled to be 7.5℃ / min, and the temperature was raised to 650℃ and kept warm for 60 minutes, and finally the heating rate was controlled to be 6℃ / min to rise to the sintering temperature of 1050℃, kept warm for 180 minutes, and the sample was taken out after the temperature dropped to 200℃. The measured performance indicators are shown in Table 1.

[0060] Example 4

[0061] 3.75 parts of Fe powder, 21.25 parts of Ni powder and 42.5 parts of Al were mixed and milled at a speed of 330r / min for 60min, and then mixed with 32.5 parts of TiC powder at a speed of 350r / min for 60min. The mixed powder was moved to a mortar, 2 parts of polyethylene glycol were added and stirred, and then pressed under a pressure of 18MPa. The pressed block was taken out and put into a tube furnace for argon protection sintering, and the argon flow rate was controlled to 100ml / min. First, the heating rate was controlled to 10℃ / min, from room temperature to 350℃ and kept warm for 30 minutes, then the heating rate was controlled to 7.5℃ / min, and it was raised to 650℃ and kept warm for 60 minutes, and finally the heating rate was controlled to 5℃ / min to rise to the sintering temperature of 950℃, kept warm for 180 minutes, and the sample was taken out after the temperature dropped to 200℃. The measured performance indicators are shown in Table 1.

[0062] Example 5

[0063] 5 parts of Fe powder, 20 parts of Ni powder and 42.5 parts of Al were mixed and milled at a speed of 330r / min for 60min, then mixed with 32.5 parts of TiC powder at a speed of 315r / min for 60min, the mixed powder was moved to a mortar, 1.75 parts of polyethylene glycol were added and stirred, and then pressed under a pressure of 18MPa, and the pressed block was taken out and put into a tube furnace for argon protection sintering, and the argon flow rate was controlled to 70ml / min. First, the heating rate was controlled to be 10℃ / min, from room temperature to 350℃ and kept warm for 30 minutes, then the heating rate was controlled to be 7.5℃ / min, and the temperature was raised to 650℃ and kept warm for 60 minutes, and finally the heating rate was controlled to be 6℃ / min to rise to the sintering temperature of 1050℃, kept warm for 180 minutes, and the sample was taken out after the temperature dropped to 200℃. The measured performance indicators are shown in Table 1.

[0064] Example 6

[0065] 6.25 parts of Fe powder, 18.75 parts of Ni powder and 42.5 parts of Al were mixed and milled at a speed of 350r / min for 60min, then mixed with 32.5 parts of TiC powder at a speed of 320r / min for 60min, the mixed powder was moved to a mortar, 2.5 parts of polyethylene glycol were added and stirred, and then pressed under a pressure of 20MPa, and the pressed block was taken out and put into a tubular furnace for argon protection sintering, and the argon flow rate was controlled to 90ml / min. First, the heating rate was controlled to be 10℃ / min, from room temperature to 350℃ and kept warm for 30 minutes, then the heating rate was controlled to be 7.5℃ / min, and it was raised to 650℃ and kept warm for 60 minutes, and finally the heating rate was controlled to be 5℃ / min to rise to the sintering temperature of 950℃, kept warm for 180 minutes, and the sample was taken out after the temperature dropped to 200℃. The measured performance indicators are shown in Table 1.

[0066] Example 7

[0067] 7.5 parts of Fe powder, 18.5 parts of Ni powder and 42.5 parts of Al were mixed and milled at a speed of 320r / min for 60min, and then mixed with 32.5 parts of TiC powder at a speed of 340r / min for 60min. The mixed powder was moved to a mortar, 3 parts of polyethylene glycol were added and stirred, and then pressed under a pressure of 16MPa. The pressed block was taken out and put into a tubular furnace for argon protection sintering, and the argon flow rate was controlled to 60ml / min. First, the heating rate was controlled to be 10℃ / min, and the temperature was raised from room temperature to 350℃ and kept warm for 30 minutes, then the heating rate was controlled to be 7.5℃ / min, and the temperature was raised to 650℃ and kept warm for 60 minutes, and finally the heating rate was controlled to be 6℃ / min to rise to the sintering temperature of 1050℃, and kept warm for 180 minutes, and the sample was taken out after the temperature dropped to 200℃. The measured performance indicators are shown in Table 1.

[0068] Example 8

[0069] 8.75 parts of Fe powder, 16.25 parts of Ni powder and 42.5 parts of Al were mixed and milled at a speed of 340r / min for 60min, and then mixed with 32.5 parts of TiC powder at a speed of 310r / min for 60min. The mixed powder was moved into a mortar, 2 parts of polyethylene glycol were added and stirred, and then pressed under a pressure of 18MPa. The pressed block was taken out and put into a tube furnace for argon protection sintering, and the argon flow rate was controlled to 90ml / min. First, the heating rate was controlled to be 10℃ / min, and the temperature was raised from room temperature to 350℃ and kept warm for 30 minutes, then the heating rate was controlled to be 7.5℃ / min, and the temperature was raised to 650℃ and kept warm for 60 minutes, and finally the heating rate was controlled to be 5℃ / min to rise to the sintering temperature of 950℃, and kept warm for 180 minutes, and the sample was taken out after the temperature dropped to 200℃. The measured performance indicators are shown in Table 1.

[0070] Example 9

[0071] 10 parts of Fe powder, 15 parts of Ni powder and 42.5 parts of Al were mixed and milled at a speed of 300r / min for 60min, then mixed with 32.5 parts of TiC powder at a speed of 340r / min for 60min, the mixed powder was moved to a mortar, 1.5 parts of polyethylene glycol were added and stirred, and then pressed under a pressure of 20MPa, and the pressed block was taken out and put into a tubular furnace for argon protection sintering, and the argon flow rate was controlled to 70ml / min. First, the heating rate was controlled to be 10℃ / min, from room temperature to 350℃ and kept warm for 30 minutes, then the heating rate was controlled to be 7.5℃ / min, and it was raised to 650℃ and kept warm for 60 minutes, and finally the heating rate was controlled to be 6℃ / min to rise to the sintering temperature of 1050℃, kept warm for 180 minutes, and the sample was taken out after the temperature dropped to 200℃. The measured performance indicators are shown in Table 1.

[0072] Example 10

[0073] 11.25 parts of Fe powder, 13.75 parts of Ni powder and 42.5 parts of Al were mixed and milled at a speed of 320r / min for 60min, then mixed with 32.5 parts of TiC powder at a speed of 340r / min for 60min, the mixed powder was moved to a mortar, 2.5 parts of polyethylene glycol were added and stirred, and then pressed under a pressure of 20MPa, and the pressed block was taken out and put into a tube furnace for argon protection sintering, and the argon flow rate was controlled to 65ml / min. First, the heating rate was controlled to be 10℃ / min, from room temperature to 350℃ and kept warm for 30 minutes, then the heating rate was controlled to be 7.5℃ / min, and it was raised to 650℃ and kept warm for 60 minutes, and finally the heating rate was controlled to be 6℃ / min to rise to the sintering temperature of 1050℃, kept warm for 180 minutes, and the sample was taken out after the temperature dropped to 200℃. The measured performance indicators are shown in Table 1.

[0074] Table 1 Measured performance indicators of metal ceramics

[0075] Sample name Relative density / % Bending strength / MPa Hardness / HRC Thermal conductivity / W / (m·K) Example 2 99.2 84.5 45.1 9.49 Example 3 99.5 94.8 50.5 4.83 Example 4 99.6 27.9 52.1 2.44 Example 5 99.6 36.9 50.5 2.65 Example 6 99.0 46.8 48.5 7.45 Example 7 99.8 21.4 48.5 0.59 Example 8 99.2 70.8 40.3 1.39 Example 9 99.6 36.8 49.5 2.74 Example 10 99.7 62.6 38.4 2.84

[0076] It can be seen from the above embodiments that the TiC-based metal ceramics obtained by the raw material ratio and preparation method of the present invention have high hardness, good density, high hardness, suitable bending strength and good thermal conductivity, and the raw materials are all common metals and compounds, do not need to be heated in a vacuum environment, only need to be sintered in an Ar protective atmosphere, the preparation process is simple and feasible, the cost is low, and it has good application value in electrical contacts and the like.

Claims

1. A method for preparing TiC / Fe / Ni / Al metal ceramics, characterized in that: The preparation method of the TiC / Fe / Ni / Al metal ceramic comprises: A. Fe powder, Al powder and Ni powder were mixed and ball-milled to obtain a mixture 1; B. Add TiC powder to mixture 1 and continue ball milling to obtain mixture 2; C. adding polyethylene glycol to mixture 2 and mixing well to obtain mixture 3; D. drying the mixture 3 at 70° C. for 7 to 8 hours; The mixture 3 after drying in step ED is pressed into shape; F. Under argon protection, the pressed mixture is heated to 950°C to 1050°C in stages 3, kept warm for at least 180 minutes, and cooled to below 200°C with the furnace to obtain a TiC / Fe / Ni / Al metal ceramic, wherein the staged heating is firstly carried out at a heating rate of 10°C / min, from room temperature to 350°C and kept warm for 30 minutes, then at a heating rate of 7.5°C / min, to 650°C and kept warm for 60 minutes, and finally at a heating rate of 5°C / min to 6°C / min to a sintering temperature of 950°C to 1050°C; By weight, TiC powder is fixed at 32.5 parts, Al powder is fixed at 42.5 parts, Fe powder and Ni powder are 25 parts in total, of which Fe powder is 1.25-11.25 parts, Ni powder is 23.75-13.75 parts, and polyethylene glycol is 1%-3% of the total weight of the above powders.

2. The method for preparing the TiC / Fe / Ni / Al metal ceramic according to claim 1, characterized in that: The Fe powder is reduced iron powder with a purity greater than 98.0% and a particle size of 200-600 meshes.

3. The method for preparing the TiC / Fe / Ni / Al metal ceramic according to claim 1 or 2, characterized in that: The Ni powder is electrolytic nickel powder with a purity greater than 99.0% and a particle size of 200-800 meshes.

4. The method for preparing the TiC / Fe / Ni / Al metal ceramic according to claim 1 or 2, characterized in that: The purity of the Al powder is greater than 99.0%, and the particle size is 400-600 meshes.

5. The method for preparing the TiC / Fe / Ni / Al metal ceramic according to claim 1 or 2, characterized in that: The purity of the TiC powder is greater than 99.0%, and the average particle size is 1.0 μm.

6. The method for preparing the TiC / Fe / Ni / Al metal ceramic according to claim 1 or 2, characterized in that: The rotation speed of the ball mill is controlled at 300 r / min to 350 r / min, and the ball milling in step A and step B is respectively performed for more than 60 minutes.

7. The method for preparing the TiC / Fe / Ni / Al metal ceramic according to claim 1 or 2, characterized in that: The pressure of the pressing process in step E is 16-20 MPa.

8. The method for preparing the TiC / Fe / Ni / Al metal ceramic according to claim 1 or 2, characterized in that: In step F, the flow rate of argon gas is controlled at 60-100 ml / min.

9. TiC / Fe / Ni / Al metal ceramic, characterized in that The TiC / Fe / Ni / Al metal ceramic is prepared by the preparation method of the TiC / Fe / Ni / Al metal ceramic according to any one of claims 1 to 8. Preferably, the hardness of the TiC / Fe / Ni / Al metal ceramic is above 38HRC, and more preferably above 45HRC.

10. The TiC / Fe / Ni / Al metal ceramic according to claim 9, characterized in that: The TiC / Fe / Ni / Al metal ceramic has a relative density of more than 99%, a flexural strength of more than 21 MPa, and a thermal conductivity of more than 0.5 W / (m·K), preferably a flexural strength of more than 45 MPa and a thermal conductivity of more than 4.5 W / (m·K).